Messianic beliefs and imperial politics in medieval Islam: the ʿAbbāsid caliphate in the early ninth century - Yücesoy, Hayrettin (Studies in comparative religion, 2009)
Introduction -- Main question -- Prophecies as text -- Messianic claims and institutionalization -- The legacy of the early caliphate -- Muslims and others: a process of conflict and confluence -- Shaping up a messianic discourse -- Qurʾānic views on the end of time -- Messianic beliefs as political ideology -- A new millennium: the year 200/800 -- Prophecies and the fourth civil war -- Crisis after Ḥārūn al-Rashīd -- The civil war as an apocalyptic fitna -- Second black banners from the East -- Making a messianic contender -- Second black banners -- Hāshimid versus ʿAbbāsid succession: designation of Alī al-riḍā -- Al-Mamūn in Baghdad -- Healing the wounds of a civil war -- Missionary activity and Byzantine raids -- God's caliph as mujaddid -- Translation activities -- Religious purity and the miḥna -- Conclusion